GE_GERICHTE C/26881/2013 vom 12. September 2014 - GE Cour de justice (2014)
HYPOTHÈQUE LÉGALE DES ARTISANS ET ENTREPRENEURS; SOUS-TRAITANT; APPROBATION(EN GÉNÉRAL); PROPRIÉTAIRE | CC.837.1; CC.837.2; CC.961.1